The effect of urban sprawl on land cover changes in agricultural areas using geographic information (Journal of Planner and Development, 2024)
Abstract: The phenomenon of urban sprawl is considered one of the important phenomena or issues that most of countries in this world suffer from, as it affects agricultural lands and the sustainability of cities, which leads to shrinkage and contraction of agricultural areas, the importance of the research lies in knowing the changes that occurred in the vegetation cover during that time period and determining the extent to which they were affected, This paper deals with the development of the phenomenon in the region between the period (2000–2020) in the city of Baghdad, GIS is used, where satellite visualizations of the region were used from the (Land sat) satellite from the US Geological Survey (USGS) website for the years (2000–2010–2020), and then classification operations depending on (NDVI,NDBI) indexs , data analysis and processing were carried out, as well as calculations were made for the process of creeping that occurred during that period within the study area in order to reach quantitative results, as it was concluded that this region has witnessed unbalanced and unsustainable growth at the expense of agricultural lands, which It affected the sustainability and development of the city.